Characterization of Four Multidrug Resistance Plasmids Captured from the Sediments of an Urban Coastal Wetland - Botts, Ryan T.; Apffel, Brooke A.; Walters, C. J.; Davidson, Kelly E.; Echols, Ryan S.; Geiger, Michael R.; Guzman, Victoria L.; Haase, Victoria S.; Montana, Michal A.; La Chat, Chip A.; Mielke, Jenna A.; Mullen, Kelly L.; et al. (Frontiers in Microbiology, 2017)
Self-transmissible and mobilizable plasmids contribute to the emergence and spread of multidrug-resistant bacteria by enabling the horizontal transfer of acquired antibiotic resistance. The objective of this study was to capture and characterize self-transmissible and mobilizable resistance plasmids from a coastal wetland impacted by urban stormwater runoff and human wastewater during the rainy season. Four plasmids were captured, two self-transmissible and two mobilizable, using both mating and enrichment approaches. Plasmid genomes, sequenced with either Illumina or PacBio platforms, revealed representatives of incompatibility groups IncP-6, IncR, IncN3, and IncF. The plasmids ranged in size from 36-144 kb and encoded known resistance genes for most of the major classes of antibiotics used to treat Gram-negative infections (tetracyclines, sulfonamides, -lactams, fluoroquinolones, aminoglycosides, and amphenicols). The mobilizable IncP-6 plasmid pLNU-11 was discovered in a strain of Citrobacter freundii enriched from the wetland sediments with tetracycline and nalidixic acid, and encodes a novel AmpC-like -lactamase (blaWDC-1), which shares less than 62% amino acid sequence identity with the PDC class of -lactamases found in Pseudomonas aeruginosa. Although the IncR plasmid pTRE-1611 was captured by mating wetland bacteria with Pseudomonas putida KT2440 as recipient, it was found to be mobilizable rather than self-transmissible. Two self-transmissible multidrug-resistance plasmids were also captured: the small (48 kb) IncN3 plasmid pTRE-131 was captured by mating wetland bacteria with E. coli HY842 where it is maintained at nearly 240 copies per cell, while the large (144 kb) IncF plasmid pTRE-2011, which was isolated from a cefotaxime-resistant environmental strain of E. coli ST744, exists at just a single copy per cell. Furthermore, pTRE-2011 bears the globally epidemic blaCTX-M-55 extended-spectrum -lactamase downstream of ISEcp1. Our results indicate that urban coastal wetlands are reservoirs of diverse self-transmissible and mobilizable plasmids of relevance to human health.